Valores centrales y sociolingüística en la comunidad de habla de Almería - Marcos, Francisco García (Studia Romanica Posnaniensia, 2019)
The article applies in the Almeria speaking community the core value sociolinguistic methodology developed by J.J. Smolicz in Australia. The results demonstrate the absolutely nuclear role of language in that community, in all target groups. The case of Almería, very probably, shows a universal pattern of sociolinguistic behaviour. In principle, it confirms the theoretical and methodological hypothesis developed in Australia. They also highlight the relevance of interdisciplinary-based research, from which valuable descriptive results can be obtained for the disciplines involved.